Literasi Digital Sebagai Sarana Pengembangan Kemampuan Berpikir Kritis Di Era Digital - Niken Wahyuningrum; Purwanti (Jurnal Ekonomi dan Bisnis Digital, 2025)
The purpose of this research is to determine the role of digital literacy as a means of developing critical thinking skills in the digital era. The method used in this research is a qualitative method, namely by reviewing literature related to the research object, such as: books, journals, magazines, newspapers, research results reports, etc. The data obtained was then analyzed using descriptive methods to describe the phenomenon studied. The results of this research show that digital literacy is a very important skill in developing critical thinking abilities in the digital era. With rapid advances in technology and information, society is required to have skills in filtering and evaluating information effectively. Challenges such as information overload and lack of awareness of the importance of source verification require serious attention. The proposed digital literacy development strategy includes comprehensive digital education, critical thinking training through digital media, and increasing technology-based creativity. This means that digital literacy is an important skill for facing the complexities of the digital era and helping people develop critical thinking skills.